Histopathological changes of mice liver induced by an Aloe vera whole leaf extract - Sodani, Ibtisam Jasim (Iraqi Journal of Science, 2022)
Plants commonly used in traditional medicine are assumed to be safe. This safety is based on their long usage in the treatment of diseases according to knowledge accumulated over centuries. One such plants is Aloe vera which has been used medicinally for centuries. Recent widespread importance of commercial Aloe vera has encouraged scientists to scientifically assess these products since it contains the anthraquinones which associated with considerable risks. In present study oral administration of 20 μl of Aloe vera extract (experimental group) (G) was given for 21 days to immature male Swiss Webster mice at weaning period. While the control groups (C) were given by the same dose and rout of administration with normal saline only. After six weeks (around puberty) the male were sacrificed to get their liver, then fixed with 10% formalin, and histological sections with a thickness of 5 microns were prepared. Aloe vera whole leaf extracts treatment resulted in liver necrosis, hepatocellular dissociation with lymphocytic cell aggregation and increase of cytoplasmic vacuolation. The sinusoids of animals fed Aloe vera whole leaf extracts were found to be widened. This study was designed to assess the histopathological changes of liver tissues of male mice administered low dose of fresh whole leaf Aloe vera extract.